Effects of the MyBFF@school program on anthropometry and body composition among overweight and obese adolescent schoolchildren - Nur Zati Iwani Ahmad Kamil; Abdul Halim Mokhtar; Abqariyah Yahya; Fuziah Md. Zain; Rusidah Selamat; Zahari Ishak; Muhammad Yazid Jalaludin (BMC Public Health)
Abstract Background Effective and feasible large-scale interventions are urgently needed to reverse the current rise in childhood obesity. The objective of this study was to evaluate the efficacy of a multicomponent intervention program, MyBFF@school, on anthropometric indices and body composition metrics among overweight and obese adolescent schoolchildren in Malaysia. Methods This is a cluster randomized controlled trial which involved schoolchildren aged 13, 14 and 16 years old from 15 out of 415 government secondary schools in central Peninsular Malaysia which were randomly assigned into six intervention (N = 579 schoolchildren) and nine control (N = 462 schoolchildren).The intervention group followed MyBFF@school program carried out by trained personnel for 6 month while the control group only followed the existing school curriculum by the Ministry of Education. The primary outcomes presented in this study were body mass index adjusted for age (BMI z-score), waist circumference (WC), percentage body fat (PBF) and skeletal muscle mass (SMM), measured at baseline, three and six months. Analyses of all outcomes except for the baseline characteristics were conducted according to the intention-to-treat principle. Mixed linear models adjusted for baseline outcome value and gender were used to evaluate the effectiveness after three and six months of intervention. Results Overall, there was no significant difference in the mean difference (MD) of BMI z-score (MD = 0.05, Confident Interval (95%CI: -0.077 to 0.194), WC (MD = 0.437, (95%CI:-3.64 to 0.892), PBF (MD = 0.977,95%CI:-1.04 to 3.0) and SMM (MD = 0.615,95%CI:-2.14,0.91) between the intervention and control group after 6 months of intervention after controlling for outcomes measured at baseline and gender. Conclusions Although the MyBFF@school programme appeared promising in engaging children and promoting awareness of healthy behaviors, it did not lead to significant improvements in the anthropometric outcomes. Possible reasons for the lack of effectiveness could include the need for more intensive or targeted interventions, parental involvement, or challenges in sustaining behavior changes outside of school settings. Trial registration Clinical trial number: NCT04155255, November 7, 2019 (Retrospective registered). National Medical Research Register: NMRR-13-439-16,563. Registered July 23, 2013. The intervention program was approved by the Medical Research and Ethics Committee (MREC), Ministry of Health Malaysia and Educational Planning and Research Division (EPRD), Ministry of Education Malaysia. It was funded by the Ministry of Health Malaysia.